Poly(ethylene glycol)s With a Single Cinnamaldehyde Acetal Unit for Fabricating Acid-Degradable Hydrogel - Zhao, Xinyue; Shan, Pengfei; Liu, Haiwei; Li, Daai; Cai, Peihan; Li, Zhongyu; Li, Zhihui (Frontiers in Chemistry, 2020)
A synthetic route to prepare a poly(ethylene glycol) with a single cinnamaldehyde acetal unit in the polymer chain, was successfully established using a newly synthesized cinnamaldehyde acetal diethylene glycol (CADEG) as initiator. This HO-PEG(ca)-OH is nontoxic and would be degraded into a cinnamaldehyde and two PEG diols in acid environment. A whole polyethylene glycol based hydrogel was easily fabricated by thiol-ene “click” reaction in alkalescence aqueous solution using acrylate-PEG(ca)-acrylate and 4-arm PEG-SH as raw materials at room temperature. The gel time was dependent on the pH of the solution and alkalinity of solution can promote gel. The hydrogel can be degradable in acidic conditions and the stronger the acidity, the faster the degradation. This HO-PEG(ca)-OH also can be used in synthesis of cinnamaldehyde containing PEG derivatives, block copolymers or other acid degradable materials.